Antitumor activity of Cetuximab in combination with Ixabepilone on triple negative breast cancer stem cells. Issue 1 (December 2016) - Tanei, Tomonori; Choi, Dong; Rodriguez, Angel; Liang, Diana; Dobrolecki, Lacey; Ghosh, Madhumita; Landis, Melissa; Chang, Jenny
Abstract Background Developing novel strategies against treatment-resistant triple negative breast cancer (TNBC) cells remains a significant challenge. The ErbB family, including epidermal growth factor receptor (EGFR), plays key roles in metastasis, tumorigenesis, cell proliferation, and drug resistance. Recently, these characteristics have been linked to a small subpopulation of cells classified as cancer stem cells (CSC) which are believed to be responsible for tumor initiation and maintenance. Ixabepilone is a new generation microtubule-stabilizing agent, which has been expected to be more efficacious than conventional taxanes. Here we aim to investigate whether the EGFR monoclonal antibody Cetuximab, in combination with Ixabepilone, is more effective in eliminating CSC populations compared to chemotherapy alone in TNBC. Methods Representative TNBC cell lines (MDA-MB-231 and SUM159) were used to evaluate breast CSC populations. We used fluorescence-activated cell sorter analysis (CD44+ and CD24-/low, or Aldefluor+ ) and a self-renewal assay called mammosphere formation efficiency (MSFE) to measure CSC population size after treatment with Cetuximab, or Cetuximab plus Ixabepilonein vitro . Results Although there was no significant decrease in cell viability, Cetuximab reduced MSFE and the CSC population in breast cancer cellsin vitro andin vivo through inhibition of autophagy. Also, SUM159 and MDA-MB-231 orthotopic tumors demonstrated partial response to Centuximab or Ixabepilone monotherapy; however, the effect of the combination treatment was significant only in SUM159 tumors (p <0.0001), when compared to Ixabepilone alone. Conclusions Overall, our findings demonstrate that EGFR-targeted therapy by Cetuximab effectively reduces the CSC population in TNBC tumors. However, combination therapy with Ixabepilone may be effective only in a small subset of TNBCs, warranting further investigation of alternative approaches to target multiple pathways for TNBC treatment.